Preliminary Phytochemical, Gas Chromatography- Mass Spectroscopy Analysis and in-vitro Anticancer Activities of Macrosolen parasiticus (L.) Danser on Human Prostate Cancer Cell line (PC-3) - Sharath, Keragodu Paramesh; Naika, Raja (Asian Journal of Biological and Life Sciences)
Background: Macrosolen parasiticus (L.) Danser, a hemiparasitic mistletoe plant was collected from the Bhadra Wildlife Sanctuary to determine its phytoconstituents and in vitro anticancer activities against PC- 3 cancer cell lines. Materials and Methods: The collected samples were subjected to a hot extraction by using a soxhlet extractor. Investigation of phytochemicals was done by preliminary qualitative and GC-MS screening. In vitro anticancer activities on PC-3 cell lines were determined by MTT assay. Results: Preliminary phytochemical analysis revealed the occurrence of a variety of phytochemicals. GCMS screening of leaf methanol extract showed the occurrence of sixteen phytoconstituents, with valuable therapeutic uses. The identified major phytoconstituents were Dihydrochrysin (45.03%); 1,6-Anhydro-beta-D-glucopyranose (15.42%), and minor constituents were Adenosine,4’-de(hydroxymethyl)-4’-[N-ethylaminoformyl]- (0.95%); 4alpha-Phorbol 12,13-didecanoate (0.84%) and Agaricic acid (0.49%). The methanolic leaf extract showed moderate cytotoxicity on PC-3 lines at higher concentrations with IC50 values of 448.7μg/ mL. while it had no cytotoxic effects on MEF-L929 non-cancerous cells. Conclusion: It is concluded that Macrosolen parasiticus contains a wide variety of secondary metabolites and also it proved a potential anticancer agent for PC- 3 cells. Therefore, more research is required to determine its biological activities.
Keywords: Gc-Ms analysis; Macrosolen parasiticus; Mistletoe; Phytochemicals; Prostate cancer (PC-3)